Better living through nutrition: How tackling malnutrition can transform Africa’s development - Covic, Namukolo (UN Sustainable Development Solutions Network, 2021)
Despite the will, many developing countries lack the resources to deal with a problem that ravages at both the national and individual level. We need smarter, context-specific solutions on nutrition that can catalyze sustainable change.